The perception of Muslim users on reliability of Islamic websites - Mohammad Nassr, Rasheed; Mahmud, Murni; Md Tap, Abu Osman; Aliyu, Mansur (Kaerntner Botanikzentrum, Klagenfurt, Austria, 2014)
The Internet offers a new medium for Muslims to conduct da’wah (preaching) and it is a direct channel to obtain Islamic knowledge anywhere at any time. However, online content can be questionable unless there is a certain level of commitment to the recommendations stated in the literature. Similarly, Islamic websites should be reliable to Muslim users as a major source of Islamic knowledge. This paper reports the findings of a study conducted to measure Muslim users’ perceptions on the reliability of Islamic websites. Around 50 participants answered online open-ended questions, although only 40 returns were considered. Content analysis was used to analyze the data and revealed that the reliability of Islamic websites must be represented in the content, endorsement, interface, and references. In addition, respondents recommended for utilizing IT technology to ensure the reliability of Islamic websites and to make cross-cultural Islamic websites which reflect the various cultures of Muslims from different races and nations, as well as to deliver the message to non-Muslims in various languages. Respondents emphasized on the neutrality of the website when discussing the perceptions of madhahāb, the availability of endorsement from well-known scholars or Islamic organizations, and the agility and accessibility of user interface. They considered that citing appropriate references will enhance the reliability of the content. Since, Muslims are distributed around the world and they come from different nations and cultures, having multi-language option for the websites is considered as a good sign of reliability. Participants suggested an application or system that could evaluate and produce reports on the reliability of Islamic websites.